Clinical use of Abemaciclib a cyclin-dependent kinase (CDK) 4/6 inhibitor in patients with breast cancer - literature review - Katarzyna Maria Krukar; Martyna Pustelniak; Katarzyna Rudnicka; Ilona Sajkiewicz; Nadia Miga-Orczykowska; Ilona Jasiuk; Justyna Wójtowicz; Paulina Lemieszek; Ewa Łukaszewska; Klaudia Kister; Kamil Chrościński; Jakub Laskowski (Kazimierz Wielki University, 2024)
Breast cancer is the most common neoplasma affecting women. Over, the past few years, the incidence of breast cancer has significantly increased, including among young women. Hormone receptor-positive (HR+) Her2 negative (HER2-) early stage breast cancer can be successfully treated using the currently available treatment methods based on endocrine theraphy (ET). However, if we consider early stage breast cancer with high risk of recurrence or metastatic disease, endocrine therapy alone may be insufficient. Unfortunately, resistance to drugs is observed in both adjuvant and palliative endocrine therapy, therefore there is a need for new treatments that are both effective and less toxic than conventional chemotherapy. One of the most successful applications of this strategy has been the use of cyclin-dependent kinase (CDK) 4 and 6 inhibitors alongside endocrine therapy significantly enhance its effectiveness. This combination has been shown to substantially increase progression-free survival while maintaining relatively low levels of toxicity. One of them is abemaciclib, whose efficacy will be shown in this research work.